Maternal Mortality and Scheme for a National Maternity Service (interim report) - Labour Party (Great Britain). Advisory Committee on Public Health. Sub-committee on Maternal Mortality
1929-11 1929 1920s 12 pages - 2 - administrative area, will be drafted by your sub-committee, and, after expert criticism thereon has been obtained, submitted to you for your approval. 4. Your sub-committee therefore recommends that the following proposal be submitted immediately to the Minister of Health: "That each Local Authority, either independently or in conjunction with other Local Authorities, be required to submit to the Minister, not later than ( ) a scheme for the provision of an adequate maternity service, involving the full use of its powers under the terms of the Maternity and Child Welfare Act 1918, and that all such schemes shall, before being approved by the Minister for grant purposes, conform substantially with the scheme appended to this Report." 5. By "an adequate maternity service" we understand one which ensures: (a) Skilled attention for every mother before, at and after the birth of her child. (b) Those ancillary services which assist in making a confinement safe and give the best chance of future health, both to mother and child. 6. The question of additional financial provision for this service is discussed in an addendum to this Report, prepared by Mr. F. Kershaw. 7. Your sub-committee, in preparing this outline scheme, has had before it the relevant paragraphs contained in the Summary of Recommendations of the Report of the Departmental Committee on the Training and Employment of Midwives, and proposes to submit their observations on the whole of these Recommendations at a later date. 8. While realising that detailed recommendations relative to scientific research are outside its scope, your subcommittee is agreed that the collection and publication of statistics relating to the complications of pregnancy and childbirth should be the function of the public health service. Records of ante-natal work, the details of every confinement and the post-natal state of each patient should be compiled, and would be of great value if the knowledge 292/824/1/115